Hubungan antara pola asuh pemberian makan dan status gizi pada anak usia 3–6 tahun di Bekasi - Khoirul Anwar; Panca Rani Sakti (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Proper feeding parenting patterns can help ensure that children get balanced and sufficient nutritional intake, which has an impact on good nutritional status.Objectives: This study aims to identify the relationship between parenting patterns and nutritional status in children aged 3-6 years.Methods: The research design used was cross-sectional with chi-square bivariate analysis test. This research was conducted at KB & TK Kupu-kupu Mungil, Bekasi Regency in May 2024. The research subjects were selected randomly using a simple random sampling technique by considering the inclusion and exclusion criteria of the research, and 80 respondents were obtained. Data were collected using the Child Feeding Questionnaire (CFQ), and anthropometric measurements of children's height and weight.Results: This study showed the results of 66,3% of parents have college, 40% work as private employees, work as private employees. The results showed that 65% of parents have good eating control, and 67,5% of children have normal nutritional status. In terms of food supervision, the majority of parents (66,3%) consistently monitor their children's consumption of sweet foods, and 52,5% often record snack consumption. Most children in the normal nutritional status category are in the good parenting group, namely 44 children (84,6%).Conclusion: Good parenting patterns can have an impact on good nutritional status in children aged 3-6 years.